ANALYSIS OF EMPLOYEE SATISFACTION OF PROCEDURAL JUSTICE AT THE EAST BELITUNG REGENCY CULTURE AND TOURISM SERVICE - Siddiq, Andhika Mochamad (Komunitas Manajemen Kompetitif, 2023)
The primary aim of this research is to identify areas that require enhancement or advancement to enhance employee satisfaction with procedural justice. It is essential to assess the most effective and efficient measures for enhancing procedural justice, given that processes are outcomes generated by an organization. To generate efficient procedures, the use of IPA is necessary as a means of evaluating the significance and effectiveness of procedural justice. The data gathering process involved the dissemination of questionnaires to a total of 70 staff working at the East Belitung Regency Culture and Tourism Office. The research findings indicate that the 6 indicators, which are further categorized into 9 questionnaire items, highlight the disparity between importance and performance. Out of the four science quadrants, the six indicators are distributed throughout three quadrants. This initiative aims to enhance procedural fairness within the Culture and Tourism Office of East Belitung Regency through efficient measures.